HOW STUDENTS ARE LEARNING TO REASON IN MATHEMATICS LESSONS - Čakāne, Ildze; Namsone, Dace; France, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The goal of mathematics teaching in primary school is not just to acquire knowledge of mathematical ideas and procedures, but also to learn mathematical reasoning. While this is common knowledge, the reality in everyday primary math classrooms in Latvia is an open question. The results from recent national diagnostics give reason to re-examine common teaching practices. The aim of this study is to clarify what is happening in primary math classrooms and to understand the needs and gaps in mathematics teaching. This will serve as the basis for designing appropriate professional development for teaching mathematical reasoning. In this study researchers observed and transcribed primary math lessons. Teacher performance was appraised using “Framework for teacher performance assessment to support teaching 21st century skills”. The criteria used to assess teacher techniques were lesson design and clarity of learning content as well as student cognitive activation. The results of this preliminary study show that separate elements of student reasoning are present in lessons.